Implementasi Digital Marketing Melalui Marketplace Pada UMKM Menjes Kyu Di Kelurahan Pakunden Kota Blitar - Adelya Putri Mahardhika; Shelly Muharrafa Hendine; Virginia Mandasari; Daisy Marthina Rosyanti (Pusat Riset dan Inovasi Nasional, 2023)
Blitar City is one of the cities in East Java Province which has a fairly large number of MSMEs. One of the potential MSMEs is located in the Pakunden Village. From the survey results it is known that there is one MSME actor producing Menjes Kyu Chips who has never used digital marketing in running his business. Bearing in mind, digital marketing is an urgent thing for MSMEs to do at this time because it has a positive correlation with business continuity in the future. This community service activity was a collaboration between UPN East Java students and the Blitar City Office of Cooperatives and Micro Small Enterprises. The purpose of this community service activity is to help solve problems as well as provide assistance to MSME actors related to the closeness of digital marketing in the form of making the Shopee marketplace as one of the marketplaces that is widely used by the community at large. The method of implementing this activity is divided into 3 stages, namely conducting socialization, training, and mentoring to the UMKM concerned. The results of this activity are expected that MSME actors can understand the importance of the role of digital marketing and be able to implement it into their business.